e-Map as An Android Application Using Shortest Path Algorithm - Carcillar, Joshua; Hernandez, Karen; Mamisay, Romnick; Rabano, Lester Paul; Matibag, Shiena; Alday, Roselie (JPAIR Multidisciplinary Research, 2016)
Using a mobile device, the user could access the map application anywhere you go. The study was developed to determine the best path from one location to another using GPS Satellite. It has three features: Searching, Detecting, and Logbook. The user can input the starting location and destination anywhere on land through searching using the Shortest Path Algorithm. Based on the inputted location given by the user, the list of available routes will be determined which enables the user to select one from a set of possible routes. Afterward, the application will detect which path that the user will take to reach their destination applicable anywhere in the world through GPS satellite. It identifies the current location of the person and once the user moves from his current location to another location, the GPS will update every 20 seconds so that all possible routes with the number of kilometers will give the user to choose the shortest route. After the completion of the Google Map application, it was found out that this application can be used worldwide. It can detect routes anywhere in the world by using arrays (from JSON) as data provided from the satellite as long as travel is on land.
Keywords: Information Technology; Google map; mobile application; shortest path algorithm; JavaScript Object Notation; Philippines